Eco-Sattva: a Buddhist response to the plastic waste crisis in Thailand - Liu, Yaoping; Run, Pharatt; Beliatte, Metteyya (Frontiers in Psychology, 2025)
The plastic waste crisis in Thailand has emerged as a substantial environmental dilemma, significantly exacerbating pollution in both marine and terrestrial ecosystems. Although previous study has mostly focused on technological and policy solutions, it is still necessary to conduct a thorough evaluation of the approach to this issue that is driven by cultural and spiritual values. This study aims to examine the influence of eco-sattva principles on the management of plastic garbage and the Buddhist communities in Thailand. It also seeks to assess the effects of Eco-Sattva’s teachings by conducting a case study at Wat Chak Daeng. A comprehensive series of interviews were carried out with a total of 15 participants, encompassing priests, community leaders, and volunteers. The transcribed data was processed and examined using the NVivo program. The interview findings demonstrate that the lessons of Eco-Sattva on plastic waste management are extremely advantageous in terms of their practical use and execution. This study investigates and analyses the three-step waste management process at Wat Chak Daeng for plastic waste management, which involves reducing, reusing, and recycling plastic trash. This study provides a significant contribution by showing that the resolution to the plastic waste crisis is not solely reliant on technical or policy-focused approaches, but may also be derived from spiritual principles.